Enhancing survival outcomes in unresectable hepatocellular carcinoma: a prospective cohort study on the effects of Huaier granules with targeted therapy plus immunotherapy - Li, Hui; Zhang, Hongliang; He, Wenting (Frontiers in Pharmacology, 2025)
ObjectiveThis study evaluated the clinical efficacy of Huaier granules combined with targeted therapy plus immunotherapy in patients with unresectable hepatocellular carcinoma (HCC) who had not undergone systemic treatment.MethodsPatients with unresectable HCC and no prior treatments were recruited from the Hospital of Traditional Chinese Medicine of Xinjiang and the First Affiliated Hospital of Xinjiang Medical University between March 2022 and July 2023. Patients received targeted therapy and immunotherapy with (exposure group) or without Huaier Granules (non-exposure group). The primary endpoint was progression-free survival (PFS), with secondary endpoints including 6-month PFS rate, HCC Symptom Severity Quantitative Response, EORTC QLQ-HCC18 Score, and safety.ResultsThe mPFS in the exposure group was 8.9 months compared to 5 months in the non-exposure group (P = 0.001; HR = 0.50). The 6-month PFS rates were 66.7% and 34.1% for the exposure and non-exposure groups, respectively (P = 0.001). The clinical efficacy rate of TCM symptom classification in HCC was higher in the exposure group (87.50% vs 59.09%; P = 0.001). The exposure group also showed improvement in fatigue (P = 0.023). Extrahepatic metastasis was an independent prognostic factor (HR = 1.77; P = 0.016), while Huaier granules reduced the risk of disease progression by 47% (HR = 0.53; P = 0.006). No significant differences were observed for adverse events. The most common adverse events were hypertension, proteinuria, abnormal liver function, and diarrhea.ConclusionHuaier granules significantly prolong PFS and improve the 6-month PFS rate, reducing disease progression risk in HCC patients. Subgroup analysis showed more pronounced benefits in patients with vascular invasion and alcohol consumption, with mPFS extending beyond 1 year.